ANALISIS KARAKTER TRUSS MORPHOMETRICS PADA IKAN KEMPRIT (Ilisha megaloptera) FAMILIA PRISTIGASTERIDAE - Tri Wijayanti; Suhestri Suryaningsih; Sri Sukmaningrum (Fakultas Biologi | Universitas Jenderal Soedirman, 2017)
The fish auction site at Ocean Fishing Port of Cilacap is one of the major fish landings sites in Indonesia. Fishes landed in this port mainly of large pelagic fish, bycatch, crustaceans including kemprit fish (Ilisha megaloptera Swainson,1839). Kemprit fish is a member of the family Pristigasteridae, which has an elongated body shape-sprawl. Fishers use this fish as the main ingredient to produce fish crackers and dried salted fish. Overfishing is the greatest threat to kemprit fish, and without conservation efforts the future population is uncertain. Fish farming is one right answer in kemprit fish conservation. However, information on this fish biology is insufficient. One of the biological aspects is sexual dimorphism, the morphological properties that can be used to distinguish between male and female fish. Truss morphometrics can measure the morphological traits differences of male and female. This technique in which the measurement of the distance Truss morphometrics in certain parts, by the benchmark points (dots Truss morphometrics), then compared with standard size. The result of the preliminary survey indicated that kemprit fish did not show sexual dimorphism, therefore truss morphometric technique applies to distinguish sexes of this fish. This research was a survey, and purposive sampling techniques were used to collect data. Data were then analyzed using the “t” test. The results showed that distinct truss distance between male and female fish was the distance between the anterior base of the dorsal fin to the anterior base of the ventral fins and the distance between the posterior base of the dorsal fin to the anterior base of the anal fin.